2013
DOI: 10.1007/s10499-013-9699-5
|View full text |Cite
|
Sign up to set email alerts
|

Selection of lactic acid bacteria as candidate probiotics and in vivo test on Artemia nauplii

Abstract: Lactic acid bacteria (LAB) were isolated from rotifer cultures in a marine hatchery to search for potential probiotics for marine animals. Fifteen strains were first selected among a total of 55, according to antibacterial activity against Vibrio sp. Among eight strains identified as Lactobacillus casei, four were highly adhesive, suggesting some ability for surface colonization. The other strains were identified as Lactobacillus plantarum, Lactobacillus dextrinicus, and Leuconostoc sp. To validate probiotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
1
26
0
2
Order By: Relevance
“…Kumar et al (2013) reported that seaweed powder plays an important role in improving overall health status and innate immunity in Rohu. Lamari et al (2014) reported that several LAB strains seem to exert a beneficial role in the structure of fish. Cao et al (2007) and Baruah et al (2005) also have reported that incorporation of microbial phytase in basal diets improved overall growth performance and bioavailability of nutrients in juvenile Rohu.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al (2013) reported that seaweed powder plays an important role in improving overall health status and innate immunity in Rohu. Lamari et al (2014) reported that several LAB strains seem to exert a beneficial role in the structure of fish. Cao et al (2007) and Baruah et al (2005) also have reported that incorporation of microbial phytase in basal diets improved overall growth performance and bioavailability of nutrients in juvenile Rohu.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported 100% Artemia mortality after 24 to 48 h of V. alginolyticus administration (Rico-Mora & Voltolina 1995, Mahdhi et al 2011, Lamari et al 2014, while other studies revealed no Artemia mortality in the same period (Gomez-Gil et al 1998). In this study, V. alginolyticus 03/8525 significantly reduced Artemia survival after 48 and 72 h of the administration, whereas the preventive colonization of Artemia with Lactobacillus pentosus H16 protects the nauplii against mortality.…”
Section: Discussionmentioning
confidence: 98%
“…los probióticos tienen un efecto benéfico en el tracto intestinal, manteniendo y fortaleciendo los mecanismos de defensa, sin alterar las funciones fisiológicas y bioquímicas [2]. los principales géneros utilizados como probióticos en cultivos son Aspergillus, Saccharomyces, Bacillus, Bacteroides y Lactobacillus [3]. la yersinia es un microorganismo infeccioso importante en humanos y animales.…”
Section: Las Bacterias áCido Lácticas Han Demostrado Una Alta Capacidunclassified